Wpływ Oscylacji Północnoatlantyckiej na przepływy rzek w dorzeczu górnej Wisły - Wrzesiński, Dariusz; Ogór, Tomasz; Plewa, Katarzyna (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2015)
This article examines the dependence between monthly and seasonal NAO indices and monthly flows of rivers in the Wisła basin down to Jagodniki. In the analysis, use was made of monthly flow data from 55 gauging stations from 1971–2010. On the basis of 156 coefficients of correlation among the variables analysed, two variants of the clustering of the gauging stations, using Ward’s method, were employed. In both, six river clusters were distinguished. In a majority of cases, the analyses showed there to be the strongest negative correlation between winter NAO indices and May to September flows of the Wisła’s left-bank tributaries. The NAO impact on the flow of the Wisła’s Carpathian tributaries is weaker, though still observable. 6 195 203 15 Badania Fizjograficzne